Breed effects and retained heterosis for growth, carcass, and meat traits in advanced generations of composite populations of beef cattle - Gregory, K.E.; Cundiff, L.V.; Koch, R.M.; Koohmaraie, M.; Dikeman, Michael E. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Retained heterosis for growth, carcass, and meat traits was estimated in F3 generation steer progeny in three composite populations finished on two levels of dietary energy density (2.82 MCal ME and 3.07 MCal ME, and 11.5 % CP) and serially slaughtered at four endpoints at intervals of 20 to 22 days. Breed effects were evaluated in the nine parental breeds of Red Poll (RP), Hereford (H), Angus (A), Limousin (L), Braunvieh (B), Pinzgauer (P), Gelbvieh (G) , Simmental (S), and Charolais (C) that contributed to the three ‘composite’ populations. MARC-I was l/4 B, l/4 C, l/4 L, l/8 H, and l/8 A; MARC-II was l/4 G, l/4 S, l/4 H, and l/4 A; and MARC-III was l/4 RP, l/4 P, l/4 H, and l/4 A. Breed effects were important for growth traits; carcass traits; and retail product, fat trim and bone percentages, and weights. Even though mean slaughter weight was 126.6 lb heavier for Simmental, Gelbvieh and Charolais breeds, they did not differ from Limousins in retail product weight because of their lower dressing percentages, higher fat trim percentages, and higher bone percentages. The effects of dietaryenergy density were important for most traits, and little interaction occurred between breed group and dietary energy density. The MARC-III composite had lighter final and carcass weights, a lower percentage of retail product, a higher percentage of fat trim, and a higher percentage of ribeye fat than the MARC-I composite, with the MARC-II composite being generally intermediate. Retained heterosis generally was significant for each composite population and for the mean of the three composite populations for weight of retail product, fat trim, and bone. For percentage of retail product and fat trim, MARC-II and MARC-III composites had a lower percentage of retail product and a higher percentage of fat trim than the mean of the contributing breeds. Composite populations or breeds provide an opportunity to use breed differences to achieve and maintain optimum additive genetic composition for carcass composition traits and to use heterosis to increase lean tissue growth rate and(or) to increase rate of fat deposition.
Keywords: Beef; Heterosis; Growth; Carcass; Meat traits